Pitfalls in the diagnosis of ectopic hamartomatous thymoma - Michal, M; Zámecník, M; Gogora, M; Mukensnabl, P; Neubauer, L (Histopathology, 1996)
We describe four cases of ectopic hamartomatous thymoma with unusual morphological features. In cases 1 and 2 we found a dysplastic glandular component which was often arranged in a cribriform pattern bridging several glandular spaces. In case 2 we found solid adenocarcinomatous areas with infiltrative edges. Case 3 showed widespread smooth muscle differentiation within the spindle epithelial cell component, the presence of multiple clear cell glands which contained a distinct myoepithelial layer and an overall picture which vaguely resembled a sclerosing adenosis of the breast. Case 4 contained frequent foci of multinucleated giant epithelial cells within the markedly cellular spindle cell component: it also showed multiple, hypocellular, myxoid areas containing eosinophilic cords and pearls of squamous cells, and resembled squamous cell carcinoma with a sarcomatoid spindle cell component. We could not find any evidence of a thymic origin or of thymic differentiation in our four cases or in any other reported cases of ectopic hamartomatous thymoma. We believe that ectopic hamartomatous thymomas manifest salivary gland differentiation.
Keywords: Clavicle; Humans; klíční kost; thymom; dospělí; hamartom; Thymoma; lidé; Biomarkers; Thoracic Neoplasms; Immunohistochemistry; imunohistochemie; Adult; biologické markery; Male; sternum; mužské pohlaví; nádory hrudníku; Hamartoma; Sternum